The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/cctc.201500524
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Polyol Synthesis Catalyzed by a Thermostable Transketolase Immobilized on Layered Double Hydroxides in Ionic liquids

Abstract: In this work we set out to study the activity of a thermostable Transketolase (TK) from Geobacillus stearothermophilus (TKgst) in an ionic liquid as cosolvent, which has never been investigated before with this enzyme. 1‐Butyl‐3‐methylimidazolium chloride ([BMIm][Cl]) in the range 30–50 % in water maintained the total activity of TKgst and increased the reaction rate in the presence of pentoses as acceptor substrates, particularly d‐ribose. To improve the synthetic process, TKgst was immobilized on an inorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…The absolute configurations of 4 – 6 were further confirmed by comparing their optical rotations with those reported in the literature. These characterization data confirmed that the three TK gst ‐catalyzed reactions each led to a single ketose with the expected l ‐ erythro (3 S ,4 S ) configuration, consistent with the stereoselectivity observed with other aldehyde acceptors by TK gst catalysis at elevated temperatures …”
Section: Resultssupporting
confidence: 78%
“…The absolute configurations of 4 – 6 were further confirmed by comparing their optical rotations with those reported in the literature. These characterization data confirmed that the three TK gst ‐catalyzed reactions each led to a single ketose with the expected l ‐ erythro (3 S ,4 S ) configuration, consistent with the stereoselectivity observed with other aldehyde acceptors by TK gst catalysis at elevated temperatures …”
Section: Resultssupporting
confidence: 78%
“…BAL is able to produce highly enantioenriched 2‐hydroxy ketones in high chemical yield, however mostly of lipophilic character , . We envisaged the synthesis of polyols, usually a domain of aldolases and transketolases, by employing BAL in carboligase reactions. Accordingly, we reasoned that 2,2‐dimethyl‐1,3‐dioxolane‐4‐carbaldehyde (glyceraldehyde acetonide, 3 ) should be suitable for an enzyme‐catalyzed access to tetrols.…”
Section: Methodsmentioning
confidence: 99%
“…1). The millifluidic technology applied to TK-catalysed carbon-carbon bond formation reactions is of fundamental utility [13][14][15] in optimizing the reaction conditions. Several assay formats have been developed to probe the substrate tolerance of TK by measuring the remaining substrate or product formed.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that TK gst activity was stable for 16 h in the aqueous solution containing 30%-50% [BMIm][Cl] enhancing TK gst activity towards pentoses, particularly D-ribose. 13 …”
Section: Introductionmentioning
confidence: 99%